Analisis Implementasi Sistem Merit dalam Proses Promosi Jabatan ASN di Indonesia Studi Kasus : Implementasi Sistem Merit dalam Proses Promosi Jabatan di Kementerian Keuangan. - Salsabila, Aurelia; Lubis, Grace Deborah; Rizky P, Muhammad; Azahra, Nafisa (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
The implementation of the Merit System in the promotion process of Civil Servants (ASN) in Indonesia, with a focus on a case study at the Ministry of Finance. The concepts of qualification, competence, and performance are the main foundations in the management of employees in the public sector. Through a literature review research method, this study highlights the challenges and progress in the implementation of the Merit System, as well as the importance of transparency, accountability, and professionalism in the promotion process. By emphasizing the values of merit, it is hoped that this system can reduce the culture of patrimonialism, improve the effectiveness of the career system, and strengthen transparency in decision-making for promotions. Although there are still challenges such as resistance to change, consistent efforts and strong political support are needed to realize an effective Merit System in the management of ASN in Indonesia.